A influência do sorriso gengival no vedamentos labial - Santos, Giselle Gasparino dos (2006)
This project consecrated the meeting of two areas of knowledge: Periodontology and Speech therapy, being conducted by a speech therapist, master in Communication Disorders and mentored by a professor of Dentistry and researcher. The experiments were performed by a multidisciplinary team, composed by speech therapist and dental surgeons who sought the relationship in individuals with excessive gingival display and oral myofunctional implications. Objective: The purpose of this study was to verify the influence of excessive gingival display on lip seal. Methods: Eighteen individuals with excessive gingival display and difficulty in lip sealing underwent oromiofunctional evaluation and surface electromyography to verify the effort of the mental muscle to perform lip seal in the pre and post surgical conditions. Aesthetic periodontal surgery was performed to remove excess gingival tissue and/or premaxilla bone volume and after 6 months the patients were reevaluated. Results: Decreased contraction and tension of the mental muscle was clinically observed during lip sealing and electromyographic analysis revealed a statistically significant difference ( 24.64µRMS – 6.46 µRMS, p= 0.004) in the mental muscle effort for lip seal after surgery. Conclusion: Lip sealing is influenced by bone and/or gingival volume and periodontal surgery contributed to a smoother contact between the lips.